Green Finance and Corporate Governance: Legal Mechanisms for Promoting Sustainable Investments - Pratik Som; Bandana Sinha; Shilpi Pramanik; Supriti Jana (The Bioscan, 2026)
A transformation in the global landscape of sustainability has brought a new definition of the function of corporations and a new face of financial systems. The era of profit-driven corporate growth is indeed over, as both the corporate world and governments now recognize the extent of climate change, biodiversity loss and resource scarcity (Richardson, 2020).